2021
DOI: 10.13080/z-a.2021.108.042
|View full text |Cite
|
Sign up to set email alerts
|

Effect of biochar addition method on ammonia volatilization and quality of chicken manure compost

Abstract: Composting chicken manure causes negative impacts on environmental ecosystem by increasing ammonia (NH 3 ) emissions. Split addition of maize straw-derived biochar (Bi) during composting of chicken manure may promote the composting process, increase the quality of produced compost and reduce NH 3 volatilization. To build composting piles, fresh chicken manure and maize straw were mixed (2:1 w/w). Biochar (10% w/w) was applied to the compost piles in different addition modes: one-time applied biochar (OTABi), 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 39 publications
(52 reference statements)
1
1
0
Order By: Relevance
“…High levels of ammonia emissions were observed during the composting of chicken manure, which prevented the trend from being visible since day one [34]. However, in other studies where chicken feces were composted with biochar, a lag phase was observed [35]. The primary reason for the NH3 loss was the acidity (pH); in the first study, the pH was 8, and in the second study, it was 9, similar to our results [20].…”
Section: Kinetics Of Nh3 Productionsupporting
confidence: 79%
“…High levels of ammonia emissions were observed during the composting of chicken manure, which prevented the trend from being visible since day one [34]. However, in other studies where chicken feces were composted with biochar, a lag phase was observed [35]. The primary reason for the NH3 loss was the acidity (pH); in the first study, the pH was 8, and in the second study, it was 9, similar to our results [20].…”
Section: Kinetics Of Nh3 Productionsupporting
confidence: 79%
“…Electrical conductivity (EC) indicates the salinity of the soil amendment (e.g., vermicompost, compost, manure, etc. ), and reflect its validity as an amendment for soil fertility and agricultural production (Abd El-Rahim et al, 2021;Lim et al, 2014) 2). Also, EC of control treatment (compost) was also decreased (Figure 2).…”
Section: Electrical Conductivity (Ec)mentioning
confidence: 99%